Reducing Societal Obesity: Establishing a Separate Exercise Model through Studies of Group Behavior - J. S. Puterbaugh (Hindawi Limited, 2016)
The past 50 years has brought attention to high and increasing levels of human obesity in most of the industrialized world. The medical profession has noticed, has evaluated, and has developed models for studying, preventing, and reversing obesity. The current model prescribes activity in specific quantities such as days, minutes, heart rates, and footfalls. Although decreased levels of activity have come from changes revolving around built environments and social networks, the existing medical model to lower body weights by increasing activity remains individually prescriptive. It is not working. The study of societal obesity precludes the individual and must involve group behavioral studies. Such studies necessitate acquiring separate tools and, therefore, require a significant change in the evaluation and treatment of obesity. Finding groups with common activities and lower levels of obesity would allow the development of new models of land use and encourage active lifestyles through shared interests.